Prosperity and security? : a study of resilience in Handelsbanken - Jarnvall, Wilhelm (SLU/Dept. of Economics, 2021)
This thesis identifies the factors that make the Swedish bank Handelsbanken resilient. Throughout the financial crises in recent memory, Handelsbanken has remained strong and managed to avoid bailouts from the Swedish government. Since the crisis of 2008, much effort from governments and independent committees has been put into strengthening the regulatory frameworks that banks abide by. Handelsbanken managed to stay strong despite these regulations proving too weak during the crises. Therefore, this thesis focuses on understanding what attributes as an organisation Handelsbanken possess to make them resilient to crises. Through a series of interviews with branch managers of different branches of Handelsbanken, the most important factors that increase the resilience of Handelsbanken are identified. The interviews provide a picture of the organisational culture and its strong ties to the company’s credit policy, revolving around making decisions locally and always remaining close to the market. A risk avert culture and organisational structure was unanimously identified as the most important factor by all interviewees. Beside this, the regulation frameworks and increased precision in credit issuing that have developed since the crisis of 2008 also increased the resilience of the bank.